4(l+1)=2(l-3)

Simple and best practice solution for 4(l+1)=2(l-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(l+1)=2(l-3) equation:



4(l+1)=2(l-3)
We move all terms to the left:
4(l+1)-(2(l-3))=0
We multiply parentheses
4l-(2(l-3))+4=0
We calculate terms in parentheses: -(2(l-3)), so:
2(l-3)
We multiply parentheses
2l-6
Back to the equation:
-(2l-6)
We get rid of parentheses
4l-2l+6+4=0
We add all the numbers together, and all the variables
2l+10=0
We move all terms containing l to the left, all other terms to the right
2l=-10
l=-10/2
l=-5

See similar equations:

| 190-(6x+2x)=-10 | | 8(4s+3)=344 | | w*5-5=5 | | 2x+124x+4=3x+9 | | -4=2t+-4 | | -7y-1=35-10y | | 4(x+2)/5=10 | | 2x+8=3.2 | | F(8)=|x| | | 2x+18=24x | | 2w-14=-14 | | (2x-2)(x)=264 | | 5u-25=45-u | | v/17+12=14 | | 3.1(4.8a-1)-3.9=a+1 | | 6x-9=51-4x* | | (2x-16)⁰+2x=180 | | 1*1/2-2y=1/4 | | 5+4×n=17 | | (x−8)(x+7)=0 | | X+x/3=132 | | 3x+8=2×-12 | | 9x-14=2x+19 | | 6x-1+8x+7=90 | | 24x–18+12x–3=36x–21 | | 13.50-c=26.50 | | -2.5=a-1.7 | | -13-40=7(-2n+2) | | (2x+5)(x–4)=0 | | 101/6=293/4h | | (3m/4)+3=18 | | 10-5m=2m |

Equations solver categories